Benchmarking mechanical properties of 3D printed elastomeric microstructures - Eivgi, Or; Vázquez-Martel, Clara; Lukeš, Jaroslav; Blasco, Eva (Small Methods, 2025)
The characterization of mechanical properties in soft three-dimensional (3D) printed materials at the microscale remains a significant challenge due to the lack of standardized methodologies. To address this issue, a microscale nanoindentation protocol for elastomeric 3D printed microstructures is developed, optimized, and benchmarked. Herein, a conospherical indenter tip (r = 10.26 µm), a modified trapezoidal displacement profile with lift-off segments to capture adhesion interactions, and the nano-Johnson-Kendall-Roberts model for data analysis are employed. The protocol is optimized and verified using four newly developed polydimethylsiloxane (PDMS)-based inks for two-photon 3D laser printing. The results are compared to a state-of-the-art literature protocol that uses a Berkovich tip and the Oliver-Pharr model. It is shown that adhesion forces play a significant role in mechanical properties overestimation, showing differences of up to 80% between the different protocols. This study highlights the importance of carefully selecting characterization protocol to yield comparable results between studies. By providing a standardized protocol, it paves the way for straightforward and accurate characterization of mechanical properties in soft 3D printed materials at the microscale.
Zuerst veröffentlicht: 12. Juni 2025
Gesehen am 16.10.2025